2013
DOI: 10.1038/mi.2012.62
|View full text |Cite
|
Sign up to set email alerts
|

STAT1-regulated lung MDSC-like cells produce IL-10 and efferocytose apoptotic neutrophils with relevance in resolution of bacterial pneumonia

Abstract: Bacterial pneumonia remains a significant burden worldwide. Although an inflammatory response in the lung is required to fight the causative agent, persistent tissue-resident neutrophils in non-resolving pneumonia can induce collateral tissue damage and precipitate acute lung injury. However, little is known about mechanisms orchestrated in the lung tissue that remove apoptotic neutrophils to restore tissue homeostasis. In mice infected with Klebsiella pneumoniae, a bacterium commonly associated with hospital-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
150
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(162 citation statements)
references
References 50 publications
11
150
0
1
Order By: Relevance
“…Most importantly, we found that IL-10 was critical for macrophages to induce the proliferation of Tregs in miR-155 ASO-treated ALI mice, suggesting that IL-10 was an important link between M2-like macrophages and Treg proliferation during recovery from ALI. Consistent with our finding, Poe et al (46) reported that IL-10-deficient mice displayed increased morbidity with progressive weight loss and persistent lung inflammation in the later phase. In addition, we failed to find the critical role of TGF-b, another important factor for Treg development, in the elevated proliferation of Tregs in miR-155 ASO-treated ALI mice, which remains to be investigated.…”
Section: Cd4supporting
confidence: 82%
See 1 more Smart Citation
“…Most importantly, we found that IL-10 was critical for macrophages to induce the proliferation of Tregs in miR-155 ASO-treated ALI mice, suggesting that IL-10 was an important link between M2-like macrophages and Treg proliferation during recovery from ALI. Consistent with our finding, Poe et al (46) reported that IL-10-deficient mice displayed increased morbidity with progressive weight loss and persistent lung inflammation in the later phase. In addition, we failed to find the critical role of TGF-b, another important factor for Treg development, in the elevated proliferation of Tregs in miR-155 ASO-treated ALI mice, which remains to be investigated.…”
Section: Cd4supporting
confidence: 82%
“…Previous studies showed the critical roles of IL-10 and TGF-b in the development of Tregs (44,45). Moreover, some evidence showed that IL-10 was an important factor in the resolution of ALI (46,47). Considering that the BAL level of IL-10 increased significantly during the recovery of miR-155 ASO-treated ALI (Fig.…”
Section: Macrophages Induced the Proliferation Of Tregs Through Il-10mentioning
confidence: 99%
“…These M-MDSCs are recruited by monocyte chemokines, proliferate locally, and contribute to an antiinflammatory milieu, best characterized in models of tumor growth (15 (Figure 3, B and C and Supplemental Figure 2D). Coincident with the influx of M-MDSCs we noted the abrupt suppression of STAT-1 signaling, a transcription factor that is usually critical in acute bacterial infection (22,23). STAT-3 signaling, important for M-MDSC proliferation (24), was also induced following infection and was more sustained than STAT1 (Supplemental Figure 4 above the basal levels.…”
Section: Resultsmentioning
confidence: 93%
“…Proteomic data and functional assays further illustrated the profound effects of the M-MDSC population in decreasing phagocytic efficiency without participating in clearance themselves. The importance of monocytes in the clearance of K. pneumoniae from the lung has been well recognized (14,22). Exactly why these strains of K. pneumoniae preferentially recruit a monocytic response remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Other than the changes in the number of neutrophils described above, we did not observe any major differences between the genotypes in terms of immune cell populations in the lungs (data not shown) except for CD11b (28). Recently, these cells have also been described as myeloid-derived suppressor cells (MDSCs), which function to restrict ongoing inflammation and favor resolution (28,29).…”
Section: Grk5 Inhibits Bacterial Clearance But Does Not Regulate Intrmentioning
confidence: 75%